Nanofluid Flow in Porous Media 2020
DOI: 10.5772/intechopen.84266
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MHD on Modified Nanofluid Model with Variable Viscosity in a Porous Medium

Abstract: A computational simulation for two-dimensional steady flow of modified nanofluid over an exponential stretching surface in a porous medium with magnet hydrodynamics and variable viscosity is presented in this study. Modified nanofluids are generalization of both hybrid nanofluids and simple nanofluids. Here, we consider three nanoparticles which drastically enhance the thermal conductivity of nanofluid. The viscous model associated with variable viscosity and MHD flow is employed. Well-known similarity transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In continuation to this hypotheses researchers have started to prepare a mixture three different nanoparticles suspended in a base fluid called modified nanofluid to optimize the heat transfer capacity. Nadeem et al [9] studied the heat transportation phenomenon on modified nanofluid in porous medium with MHD, and established that modified nanofluids are more effective in heat transfer then hybrid and nanofluid cases. Furthermore Nadeem et al [10] presented, modified nanofluids flow through a stretching Rega plate where viscosity is temperature dependent.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation to this hypotheses researchers have started to prepare a mixture three different nanoparticles suspended in a base fluid called modified nanofluid to optimize the heat transfer capacity. Nadeem et al [9] studied the heat transportation phenomenon on modified nanofluid in porous medium with MHD, and established that modified nanofluids are more effective in heat transfer then hybrid and nanofluid cases. Furthermore Nadeem et al [10] presented, modified nanofluids flow through a stretching Rega plate where viscosity is temperature dependent.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, technical advances have made improvements in the rheological properties of cooling fluids, and the manufacture of a steady solid-liquid suspension called nanofluid has optimized the thermal performance of industrial instruments and heat exchangers [1]. erefore, several researchers have reported enhancement in heat transfer through nanofluids [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…They found that Cu-Al 2 O 3 /water has greater heat transfer rate than nanofluid and regular fluid for some of the investigated parameters. In addition, a considerable amount of previous works on hybrid nanofluid over a porous medium have been successfully reported (e.g., [31][32][33][34][35]).…”
Section: Introductionmentioning
confidence: 99%